ANALISA PRODUKTIVITAS TENAGA KERJA HARIAN DAN BORONGAN PADA PROYEK RSUD DR. SOEGIRI LAMONGAN - M. Arif Surachman; Prima Eko Agustyawan (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2019)
In the world of construction services, labor productivity is one of the critical success factors of a development project. In measuring the level of labor productivity there are various ways, one of which is to examine thelevel of LUR (Labor Utilitation Rate) of each worker, which examines to what level of effectiveness of workers in the work. The magnitude of the level of labor productivity is influenced by many factors, such as age, work experience, education level, wage conformity, number of family dependents, worker health, inter-worker relationship, managerial and work group compositionThe research was conducted in Dr. Hospital's development project. Soegiri Lamongan. The research was conducted by observing the productivity level of 20 workers and accompanied by filling the questionnaire. Observation of productivity level (LUR) conducted for 3 days on each worker. From the results of data collection, both productivity data and questionnaires performed data processing process with the help of MS program computer. Excel.From the analysis of data that has been done can be seen that the level of productivity (LUR) of the average worker on brick work in the building project Dr. Hospital. Soegiri of 75.83%, it means quite productive because more than 50%. Variables that have been determined in fact significasinya <0.005 (sig required) then the simulatan have an effect on the level of productivity.The predetermined variable that is age, work experience, education level, wage appropriateness, number of family dependent, worker health, inter-worker relationship, managerial and work group composition simultaneously have a significant influence on the productivity of the masonry work. Partially or individually variables that have a significant influence on the level of labor productivity is the variable age and work experience variables.